Effects of parsley (Petroselinum crispum) on the aorta and heart of Stz induced diabetic rats - (:unkn) unknown (Springer Netherlands, 2003)
Parsley is one of the medicinal herbs used by diabetics in Turkey. It has been reported to reduce blood glucose levels. In this study the effects of feeding parsley on diabetes-induced free radical mediated injury in rat aorta and heart tissues were investigated. Swiss albino rats were divided into six groups: Control, diabetic, parsley, diabetic + parsley, glibornurid, and diabetic + glibornurid. Rats were subjected to i.p. streptozotocin (STZ, 65 mg/kg) to induce diabetes. On the fourteenth day of the study, either parsley (2 g/kg) or glibornurid (5 mg/kg) were given for 28 days to the diabetic rats. Aorta and heart tissue lipid peroxidation and glutathione levels as well as blood glucose levels were determined. The results of the present study indicate that lipid peroxidation was increased and glutathione levels were decreased in both aorta and heart tissue of the diabetic rats. However, treatment of the diabetic rats with either parsley or glibornurid reversed the effects of diabetes on blood glucose, and tissue lipid peroxidation and glutathione levels. ©2003 Kluwer Academic Publishers.
Keywords: Glutathione; Lipid peroxidation; Parsley; Streptozotocin